Determination of risk factors for fever after transarterial chemoembolization with drug-eluting beads for hepatocellular carcinoma. Issue 44 (5th November 2021) - Li, Jinpeng; Shi, Congcong; Shi, Jutian; Song, Jinlong; Wang, Nan
Abstract : Abstract: This study was to identify risk factors affecting postembolization fever (PEF) of CalliSpheres drug-eluting bead transarterial chemoembolization (DEB-TACE) in the treatment of primary hepatocellular carcinoma (HCC). One hundred eighty-eight consecutive patients with HCC who underwent DEB-TACE with fever between June 2017 and May 2019 were included in this retrospective study. The patients were divided into 4 groups based on the severity of posttransarterial chemoembolization (TACE) fever according to the degrees of body temperature. Univariate analysis and multivariate logistics regression were performed to identify potential risk factors for post-TACE fever. In the stepwise multiple regression analysis, pre-TACE blood urea, small particle size and Cental liqefction ( P < .05) were independent risk factors of severe post-TACE fever ( P < .05, respectively). Portal vein thrombosis ( P < .01), Child-Pugh stage ( P < .01), and cycles of DEB-TACE ( P < .05) were independent risk factors for clinical death, PEF was not associated with clinical death ( P = .754) and 6-month survival ( P = .524) in the univariate analysis. Moreover, multivariate Cox regression was performed, and Child-Pugh stage (B vs A) ( P = .040) and portal vein thrombosis (yes vs no) ( P = .033) were independent factors predicting unfavorable overall survival in HCC patients. Pre-TACE blood urea, small particle size, and Cental liqefction were significantly correlated with the occurrence fever after DEB-TACE. Therefore, these factors should be taken into full consideration for the relief of fever. However, PEF after D-TACE was not associated with clinical death and 6-month survival rate.